Transcription Factor c-Maf Promotes Immunoregulation of Programmed Cell Death 1–Expressed CD8 + T Cells in Multiple Sclerosis - Koto, Shusuke; Chihara, Norio; Akatani, Ritsu; Nakano, Hiroko; Hara, Atsushi; Sekiguchi, Kenji; Matsumoto, Riki; Toda, Tatsushi (Neurology : neuroimmunology & neuroinflammation, 2022)
Multiple sclerosis (MS) is an inflammatory demyelinating disease of the CNS. CD8 T cells are prominently found at inflammatory sites. Recent advances in understanding checkpoint molecules, including programmed cell death 1 (PD-1), expressed on CD8 T cells, highlight the immune regulatory roles of this T-cell subset; however, the role of CD8 T cells in MS is unclear. Thus, we aimed to reveal the characteristics of PD-1-expressed (PD-1 ) CD8 T cells in MS. We performed a cohort, case-control study for phenotyping analysis of PD-1 CD8 T cells in disease remission and flare states using CSF and peripheral blood samples of 45 patients with MS or clinically isolated syndrome and 12 healthy subjects. We further analyzed the transcriptome of sorted PD-1 CD8 T cells obtained from interferon (IFN)-β-treated patients and validated their regulatory machinery using in vitro cell culture assays with lentiviral gene transfer. In the disease remission state, PD-1 CD8 T cells were decreased in the peripheral blood of patients with MS and resolved in patients treated with IFN-β treatment who showed immune regulatory cytokine interleukin (IL)-10 expression. In the disease flare state, we found that PD-1 CD8 T cells were enriched in the CSF, which predicted a good response to subsequent IV steroid therapy. Transcriptome analysis of sorted PD-1 CD8 T cells revealed the transcription factor c-Maf as a potential major regulator of the gene module, including multiple coinhibitory molecules. Furthermore, c-Maf expressed in CD8 T cells induced PD-1 expression and production of IL-10 as well as suppressed alloactivated CD4 T-cell survival. This study uncovered a favorable role of PD-1 CD8 T cells against MS and demonstrated that c-Maf-driven IL-10 is an immune regulatory machinery.